The effects of experimental potato protein on starter pig growth performance - Kerr, C.A.; Bergstrom, J.R.; Musser, R.E.; Nessmith, W.B.Jr; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This study suggested that experimental potato protein can be an effective replacement for a portion of spray-dried animal plasma in starter diets. Pigs fed combinations of experimental potato protein and spray-dried plasma had greater ADG than those fed either protein source alone. In phase II diets, pigs fed experimental potato protein had similar ADG and FIG compared with those fed spray-dried blood meal and select menhaden fish meal.
Keywords: Swine; Starter pig performance; Potato protein